Review: Livestock cell types with myogenic differentiation potential: Considerations for the development of cultured meat - M. Olenic; C. Deelkens; E. Heyman; E. De Vlieghere; X. Zheng; J. van Hengel; C. De Schauwer; B. Devriendt; S. De Smet; L. Thorrez (Animal)
With the current environmental impact of large-scale animal production and societal concerns about the welfare of farm animals, researchers are questioning whether we can cultivate animal cells for the purpose of food production. This review focuses on a pivotal aspect of the cellular agriculture domain: cells. We summarised information on the various cell types from farm animals currently used for the development of cultured meat, including mesenchymal stromal cells, myoblasts, and pluripotent stem cells. The review delves into the advantages and limitations of each cell type and considers factors like the selection of the appropriate cell source, as well as cell culture conditions that influence cell performance. As current research in cultured meat seeks to create muscle fibers to mimic the texture and nutritional profile of meat, we focused on the myogenic differentiation capacity of the cells. The most commonly used cell type for this purpose are myoblasts or satellite cells, but given their limited proliferation capacity, efforts are underway to formulate myogenic differentiation protocols for mesenchymal stromal cells and pluripotent stem cells. The multipotent character of the latter cell types might enable the creation of other tissues found in meat, such as adipose and connective tissues. This review can help guiding the selection of a cell type or culture conditions in the context of cultured meat development.